Answer:
[tex]6b^{5}-3b^{4}-35b^{3}-10b^{2}+43b+63[/tex]
Step-by-step explanation:
we have to find the multiplication of following polynomials
As we know that the multiplication of two polynomials are done in following way
let we have two polynomial (ax+b) and (cx+d) their product would be
(ax+b)(cx+d)
=ax(cx+d)+b(cx+d)
=acx² + axd + bcx + bd
Now similarly for the given polynomial we have
[tex](3b^{3}-4b-7)*(2b^{2}-b-9)[/tex]
it could be written as
=3b³(2b²-b-9) -4b(2b²-b-9) -7(2b²-b-9)
Multiplying inside with values
=[tex]6b^{5}-3b^{4}-27b^{3}-8b^{3}+4b^{2}+36b-14b^{2}+7b+63[/tex]
Combining same values
=[tex]6b^{5}-3b^{4}-27b^{3}-8b^{3}+4b^{2}-14b^{2}+36b+7b+63[/tex]
=[tex]6b^{5}-3b^{4}-35b^{3}-10b^{2}+43b+63[/tex]